The SAMI Galaxy Survey: observing the environmental quenching of star formation in GAMA groups. Issue 3 (30th November 2018) - Schaefer, A L; Croom, S M; Scott, N; Brough, S; Allen, J T; Bekki, K; Bland-Hawthorn, J; Bloom, J V; Bryant, J J; Cortese, L; Davies, L J M; Federrath, C; et al.
Abstract: We explore the radial distribution of star formation in galaxies in the SAMI Galaxy Survey as a function of their Local Group environment. Using a sample of galaxies in groups (with halo masses less than $\simeq 10^{14} \, \mathrm{M_{\odot }}$ ) from the Galaxy And Mass Assembly Survey, we find signatures of environmental quenching in high-mass groups ($M_{\mathrm{ G}}\, \gt\, 10^{12.5} \, \mathrm{M_{\odot }}$ ). The mean integrated specific star formation rate (sSFR) of star-forming galaxies in high-mass groups is lower than for galaxies in low-mass groups or those that are ungrouped, with $\Delta \log (\mathrm{ sSFR}/\mathrm{yr^{-1}}) \, =\, 0.45 \pm 0.07$ . This difference is seen at all galaxy stellar masses. In high-mass groups, star-forming galaxies more massive than $M_{*} \sim 10^{10} \, \mathrm{M_{\odot }}$ have centrally concentrated star formation. These galaxies also lie below the star formation main sequence, which suggests they may be undergoing outside-in quenching. Lower mass galaxies in high-mass groups do not show evidence of concentrated star formation. In groups less massive than $M_{\mathrm{ G}} = 10^{12.5} \, \mathrm{M_{\odot }}$, we do not observe these trends. In this regime, we find a modest correlation between centrally concentrated star formation and an enhancement in the total star formation rate, consistent with triggered star formation in these galaxies.